The Oxford handbook of the Ethiopian economy - Fantu Cheru, 1949-; Cramer, Christopher (Professor of political economy); Oqubay, Arkebe (Oxford : Oxford University Press, 2019)
From a war-torn and famine-plagued country at the beginning of the 1990s, Ethiopia is today emerging as one of the fastest-growing economies in Africa. This Oxford Handbook focuses on structural transformation to understand Ethiopia's unique model of development.
Ethiopia's Transition from a Traditional to a Developing Economy (1890s-1960s) / Bekele Shiferaw -- Infrastructure and Economic Transformation in Ethiopia / Seid Nuru -- Financial Balances and the Development of the Ethiopian Economy / Ken Coutts, Christina Laskaridis -- Trade Policy in Ethiopia (1991-2016) / Berihu A. Gebrehiwot -- Livelihoods and Mobility in the Border Regions of Ethiopia / Laura Hammond PhD -- Green and Climate Resilient Transformation in Ethiopia / Haileselassie Medhin, Alemu Mekonnen PhD -- Assessing Poverty Trends in Ethiopia (1990-2015) / John Sender -- Poverty and inequality in Ethiopia (1996/96-2015/16) / Mesele Araya, Tassew Woldehana PhD -- Growth, Poverty, and Distribution in Ethiopia / Abebe Shimeles -- Ethiopia's Changing Demography / Assefa Hailemariam PhD -- Land Tenure and Land Policy in Ethiopia (1950-2000) / Teferi Abate Adem -- Economic Policy and Food Security in Ethiopia / Deborah Johnston PhD, Helen Walls -- Changes in Child Undernutrition in Ethiopia (2000-2016) / Jenna Golan, Derek Headey PhD, Kalle Hirvonen, John Hoddinott -- Social Protection in Ethiopia / John Hoddinott, Alemayehu Seyoum Taffesse PhD -- Education and Economic Development in Ethiopia (1991-2017) / Zinabu Samaro Rekiso -- The Transformation of Smallholder Crop Production in Ethiopia (1994-2016) / Alemayehu Seyoum Taffesse PhD -- Rural Finance and Smallholder Farming in Ethiopia / Kibrom Abay, Guush Berhane PhD -- Performance and Institutions of the Ethiopian Coffee Sector / Tadesse Kuma Worako PhD, Bart Minten PhD, Florian T. Schäefer PhD -- Policy, Political Economy, and Performance in Ethiopia's Coffee Sector / Christopher Cramer, John Sender -- Agricultural Markets in Ethiopia / Bart Minten PhD, Thomas Reardon, Seneshaw Tamru -- Livestock Production in Ethiopia / Fantu N. Bachewe, Fanaye Tadesse -- Federalism in Ethiopia's Transformation / Kidane Mengisteab -- Ag
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 5, 2019).
Keywords: Economic development -- Ethiopia; Ethiopia -- Economic conditions -- 21st century; Ethiopia -- Economic conditions -- 1974-; Ethiopia -- Economic policy